INTERNATIONAL TRADE RELATIONS, ECONOMIC OPENNESS, HUMAN CAPITAL AND ECONOMIC GROWTH OF APEC UPPER MIDDLE INCOME COUNTRIES: A SHARIAH ECONOMIC PERSPECTIVE - Kholiq, Mu’amalatul; Noviarita, Heni; Kurniawan, Muhammad (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
The main problems faced by Indonesia, Malaysia, and Thailand related to international trade, economic openness, and human capital and economic growth include dependence on exports of low-value-added commodities, shaping a global economy that affects trade volume, and limitations in attracting quality Foreign Direct Investment (FDI). In addition, the quality of human resources that is not optimal due to lack of investment in education and training hinders labor productivity, thus limiting the ability of these countries to take full advantage of economic openness to drive sustainable economic growth. This study aims to analyze the relationship between international trade relations, economic openness, human capital on the economic growth of APEC upper middle income countries, namely Indonesia, Malaysia and Thailand. The research methodology used in this study is quantitative with the nature of explanatory research. The data used are secondary data in the form of panel data with a period of 2014-2023 obtained from the World Bank. The analysis uses Eviews 10 software. The results of the study provide facts that imports and human capital have an effect on economic growth while exports and economic openness, namely Foreign Direct Investment (FDI) have no effect on the economic growth of Asia Pacific Economic Cooperation (APEC) Upper Middle Income countries, namely Indonesia, Malaysia, and Thailand. In Islamic economics, international trade, economic openness, human capital, and economic growth are interrelated and must be implemented based on Islamic principles. The application of Islamic values in economic activities is expected to create a just, prosperous, and sustainable society, in accordance with the main objective of Islamic law to achieve the welfare of humanity.